Decentralization and Local Community Welfare: Analysis Based on Literature Studies - Ridwan Kurnia Rahim; Aldri Frinaldi; Lince Magriasti (Adabi : Journal of Public Administration and Business, 2024)
This article analyzes the effect of decentralization on the well-being of local communities by studying existing literature. Decentralization is the process of transferring power and control from the central government to local governments. Its goal is to enhance local autonomy, improve public services, and promote community engagement. This study examines the several types of decentralization, including administrative, fiscal, and political, and how they affect local governance. The study findings indicate that the effectiveness of decentralization is closely linked to the caliber of governance, local administrative and budgetary capabilities, and the dedication of central and local governments to empowering communities. This article also emphasizes that the appropriate implementation of decentralization can improve economic growth, social welfare, and community engagement. However, if not effectively managed, decentralization can worsen regional inequality.